A Longitudinal Study of Epileptic Seizures in Alzheimer's Disease - Baker, John; Libretto, Tina; Henley, William; Zeman, Adam (Frontiers in Neurology, 2019)
The prevalence of epileptic seizures is increased in patients in the clinical stages of Alzheimer’s disease (AD) when compared to age-matched cognitively normal populations. In previously reported work from the PrESIDe study we identified a clinical suspicion of epilepsy in between 12.75% and 28.43% of patients with AD recruited from a memory clinic. Patients with epilepsy performed similarly to patients without epilepsy on cognitive testing at the time of recruitment but were more impaired on two measures of everyday functioning (Cambridge Behavioral Inventory - Revised and Clinical Dementia Rating (CBI-R and CDR). On repeated testing in this 12-month follow-up study, patients in whom a suspicion of epilepsy was identified performed significantly worse on cognitive function testing (p=0.028) in addition to maintaining a difference on the informant questionnaires (CBI-R p<0.001), CDR p=0.020). These findings suggest that seizures in this population are a marker of a more rapid decline and worse prognosis.